Risk factors for mortality during antiretroviral therapy in older populations in resource‐limited settings. Issue 1 (14th January 2016) - O'Brien, Daniel; Spelman, Tim; Greig, Jane; McMahon, James; Ssonko, Charles; Casas, Esther; Mesic, Anita; Du Cros, Philipp; Ford, Nathan
Abstract : Introduction: An increasing proportion of adult patients initiating antiretroviral therapy (ART) in resource‐limited settings are aged >50 years. Older populations on ART appear to have heightened risk of death, but little is known about factors influencing mortality in this population. Methods: We performed a retrospective observational multisite cohort study including all adult patients (≥15 years) initiating ART between 2003 and 2013 in programmes supported by Médecins Sans Frontières across 12 countries in Asia, Africa and Europe. Patients were stratified into two age groups, >50 years and 15 to 50 years. A Cox proportional hazards model was used to explore factors associated with mortality. Results: The study included 41, 088 patients: 2591 (6.3%) were aged >50 years and 38, 497 (93.7%) were aged 15 to 50 years. The mortality rate was significantly higher in the age group >50 years [367 (14.2%) deaths; mortality rate 7.67 deaths per 100 person‐years (95% confidence interval, CI: 6.93 to 8.50)] compared to the age group 15 to 50 years [3788 (9.8%) deaths; mortality rate 4.18 deaths per 100 person‐years (95% CI: 4.05 to 4.31)], p< 0.0001. Higher CD4 levels at baseline were associated with significantly reduced mortality rates in the 15 to 50 age group but this association was not seen in the >50 age group. WHO Stage 4 conditions were more strongly associated with increased mortality rates in the 15 to 50 age group compared to populations >50 years. WHO Stage 3 conditions were associated with an increased mortality rate in the 15 to 50 age group but not in the >50 age group. Programme region did not affect mortality rates in the >50 age group; however being in an Asian programme was associated with a 36% reduced mortality rate in populations aged 15 to 50 years compared to being in an African programme. There was a higher overall incidence of Stage 3 WHO conditions in people >50 years (12.8/100 person‐years) compared to those 15 to 50 years (8.1/100 person‐years) ( p <0.01). The rate of Stage 4 WHO conditions was similar (5.8/100 versus 6.1/100 respectively, p =0.52). Mortality rates on ART associated with the majority of specific WHO conditions were similar between the 15 to 50 and >50 age groups. Conclusions: Older patients on ART in resource‐limited settings have increased mortality rates, but compared to younger populations this appears to be less influenced by baseline CD4 count and WHO clinical stage. HIV treatment programmes in resource‐limited settings need to consider risk factors associated with mortality on ART in older populations, which may differ to those related to younger adults.